Determination of Second-Order Effects and Design for Stability Using the Drift Limit - Sabelli, Rafael; Griffis, Lawrence; Geschwindner, Louis F. (Engineering Journal, 2021)
Buildings for which second-order effects are significant are often governed by drift limits. Amplifier-based approximate second-order analysis, as presented in AISC Specification Appendix 8 (2016), typically utilizes factors based on first-order drift, for which a preliminary design and an analysis are required. This paper derives equations for the amplifier used in approximate second-order analysis, B2, based on the second-order drift. Upper-bound values of amplifiers based on the drift limit can thus be determined in advance of design, eliminating the need for iteration and simplifying the design process; these values are not excessively conservative for drift-governed designs.